Coaching doctors to improve ethical decision-making in adult hospitalized patients potentially receiving excessive treatment: Process evaluation study of the CODE intervention in doctors and nurses working in ten acute hospital wards - Ruth Piers; Let Dillen; Katrijn Goethals; An Lievrouw; Karen Versluys; Aglaja De Pauw; Celine Jacobs; Ine Moors; Fritz Offner; Anja Velghe; Nele Van Den Noortgate; Pieter Depuydt; et al. (PLoS ONE, 2025)
Introduction High quality hospital care for serious ill persons requires exemplary team-based communication and decision-making. However, there is a need for evidence-based interventions in this area. This study’s aim is to gain insight in the adoption and implementation of the COaching Doctors to improve Ethical decision-making (CODE) intervention, composed of one-on-one professional coaching in doctors and an alert to identify patients potentially receiving excessive treatment. Methods Mixed-method process evaluation study using focus group interviews, sub-analysis of the ethical decision-making climate questionnaire (EDMCQ) in nurses and doctors and a satisfaction survey in doctors. Results Of the 423 clinicians, 198 (60.2%) nurses and 63 (67.0%) doctors filled-out the EDMCQ and 20 nurses and 12 doctors participated to the focus-group interviews respectively. Thirty-five (70%) of the 50 coached doctors filled-out the satisfaction survey. Doctors estimated their leadership skills higher than the nurses prior to the study period (P = 0.006) but no longer after the study period (P = 0.366). Nurses estimated ethical awareness and reflection higher (respectively, P = 0.002 and P = 0.049) and non-avoiding end-of-life decisions and active involvement of nurses lower than the doctors (respectively P < 0.001 and P = 0.023) after the study period but not before the study period (all P-values >0.05). Doctors testified of increased awareness in ethical decision-making, more open interactions with patients and nurses, and more courage to intervene instead of doing nothing. Nurses spoke of an increased awareness to act as patient advocate, increased deliberation among peer nurses and frustration when they felt no effect of activating the CODE alert. Both doctors and nurses advised for more active involvement of nurses. The mean overall satisfaction score in doctors was 8.69 on 10. Conclusion The CODE study intervention was effective in raising awareness and self-reflection, yet did not succeed to close the (communication) gap between doctors and nurses in team-based ethical decision-making. Trial registration ClinicalTrials.gov identifier: NCT 05167019.